The Effect of Transparency and Accountability on Village Income Shopping Budget Management (APBDes) - Fitri Abrar; Chofiuddin Muchlish; Iqbal Noor (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
This study aims to determine: 1. To find out the extent of the influence of transparency on the management of the village income budget (APBdes), 2. To find out the extent of the influence of accountability on the management of the village income budget (APBdes) 3. To determine the extent of the effect of transparency and accountability for the management of the village expenditure budget (APBdes). The variables consist of Transparency and Accountability as independent variables, village financial management as the dependent variable. The method used in this study is quantitative method, the type of data used in this study is primary data, namely research data obtained directly from original sources (respondents not through intermediary media). Primary data is specifically collected through questionnaires that already contain questions related to research that is being carried out with comparisons of previous research. In the process, this research produces data that there is a significant influence between Transparency and Accountability on the Management of the Village Revenue and Expenditure Budget (APBDes).